Health technology assessment of video otoscopy for the diagnosis of otitis media in children in comparison to conventional otoscopy in primary healthcare settings in India - Ragini Bhatia; Anil Chauhan; Gyanaranjan Nayak; Pranita Pradhan; Kulbir Kaur; Joseph L. Mathew; Meenu Singh (Elsevier, 2024)
Objective: This Health Technology Assessment (HTA) was undertaken to assess the clinical-effectiveness, cost-effectiveness, and operational feasibility of using otoscopes in primary healthcare settings in India, for diagnosing otitis media in children. Methods: We undertook a three-step process sequentially determining (i) clinical effectiveness of video as well as conventional otoscopy (compared to otic microscope as the reference standard); (ii)cost-effectiveness analysis of the video otoscope; and (iii)operational feasibility and health equity considerations. The systematic review for clinical effectiveness involved literature search across five databases, screening and inclusion of relevant studies, and data synthesis. Cost-effectiveness analysis was performed using data from published literature, specialist interviews, and cost assumptions if neither was available. The Progress Plus tool was used to explore health equity and operational feasibility was taken into account. Results: The systematic review on clinical effectiveness include three relevant studies from a total of 1361 identified. The pooled sensitivity and specificity of video otoscope were 0.70 (95%CI 0.60, 0.84) and 0.92 (CI95% 0.89, 0.95) to be 0.88 (95% CI, 0.84 to 0.91). The cost-effectiveness analysis identified the incremental cost-effectiveness ratio (compared to conventional otoscope) as INR 1008.4 per QALY, with an overall gain of 413 QALYs per year. This was well below the willingness-to-pay threshold for India. There was potential of enhancing health equity and no insurmountable operational barriers, to the use of video otoscope in primary healthcare settings. Conclusion: This HTA concluded that video otoscope is clinically effective, cost-effective, and operationally feasible in Indian primary health settings, for diagnosing otitis media in children.